Caregiver adaptation after stroke: The role of adversity quotient and spiritual-religious coping - Vione Deisi Oktavina Sumakul; Fransiskus Xaverius Dotulong; Meylani Dewi Wowor; Brigita Maria Karouw; Fatin Lailatul Badriyah (Psikohumaniora: Jurnal Penelitian Psikologi, 2025)
Stroke is one of the leading causes of long-term disability, often requiring intensive support from family caregivers, whose psychological adaptation to their changing roles is essential not only for the patient’s recovery, but also for their own emotional well-being. This study aims to examine the influence of adversity quotient and spiritual-religious coping on caregivers’ perceptions and coping strategies, as well as the impact of these strategies on caregivers’ adaptation. A cross-sectional, correlational quantitative design was employed. Data were collected from 200 caregivers of post-stroke patients in Tomohon City, North Sulawesi, Indonesia selected through cluster random sampling, and using structured questionnaires. Adversity Quotient (AQ) was measured using the Chinese version of the Adversity Quotient Scale, while Spiritual-Religious Coping (SRC) was assessed by Pargament’s RCOPE scale. Caregiver perception was measured by the Appraisal of Caregiving Scale (ACS); coping strategy by the Ways of Coping Questionnaire (WCQ); and Caregiver Adaptation developed from the Coping and Adaptation Processing Scale. Data were analyzed using structural equation modeling (SEM) with SmartPLS. The results demonstrate that adversity quotient significantly influenced caregiver perception (β = .247, t = 3.259, p = .001, R² = .154, SRMR = .055) and coping strategies (β = .205, t = 3.092, p = .002, R² = .280). Similarly, spiritual-religious coping had a significant effect on caregiver perception (β = .230, t = 2.700, p = .007) and coping strategies (β = .312, t = 4.646, p < .001). Furthermore, caregiver perception positively predicted coping strategies (β = .185, t = 2.615, p = .009), and coping strategies significantly enhanced caregiver adaptation (β = .255, t = 4.035, p < .001, R² = .065). The practical implications of this study highlight the need to integrate resilience-building and spiritually informed psychological interventions into caregiver support programs to strengthen adaptive coping and promote sustained adjustment in post-stroke home care.